Effect of integrative NPK soil and foliar nutrition on winter wheat (Triticum aestivum L.) productivity in irrigated arid lands - Sultonov, Komolitdin; Kholmurodova, Guzal; Eshonkulov, Jamoliddin; Allanov, Kholik; Sindarov, Obidjon; Khayitov, Kholmurod; Khaitbaeva, Jamila; Salomov, Shavkat; Isaev, Sabirjan; Djumanazarova, Altingul; Imyaminova, Risolatxon; Jurayeva, Nodirakhan; et al. (Frontiers in Sustainable Food Systems, 2025)
The effects of chemical fertilizers on crop growth and grain yield are relatively well-known, but little is known about their synergistic effects with foliar nutrition. The factorial experiment was conducted using a strip-plot design. The main plots consisted of three chemical fertilization treatments at the following rates: N150P105K75, N180P125K90, and N210P145K105. The sub-plots included four combinations of foliar feeding with carbamide [CO(NH2)2], applied at doses of 4.0, 8.0, and 12.0 kg ha−1 at the tillering, booting, and heading stages of winter wheat (WW), respectively. The results indicated that the WW grain production was increased by 21.2% with foliar nutrition applied at a 4:8:12 kg/ha regime under the N180P125K90 chemical fertilization norm compared to the control, exhibiting the highest yield among tested variables. The total grain yield of WW increased with an increase in chemical fertilization norms, providing a significant increase in the fodder yield parameters. Increasing chemical fertilization increased the grain quality indices, but the highest indicators were observed under the moderate (N180P125K90) chemical fertilization norm applied with the foliar nutrition (4.8:12 kg/ha regime). Overall, this innovative farming technique has the potential to limit land degradation and create sustainable farming systems while improving biodiversity conservation and ecosystem services that require less chemical fertilization.